Students' perception to an interactive web-based response system in oral and maxillofacial pathology teaching - Luana Rafaela Garcez da SILVA; Hélen Kaline Farias BEZERRA; Augusto César Leal da Silva LEONEL; Elaine Judite de Amorim CARVALHO; Jurema Freire Lisboa de CASTRO; Alan Roger SANTOS-SILVA; Danyel Elias da Cruz PEREZ (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study evaluated dental students' perceptions and adherence to an interactive web-based response system in the teaching of Oral and Maxillofacial Pathology. Between 2018 and 2019, students from a single Brazilian dental school used the Poll Everywhere® app to answer questions on subjects taught during an Oral and Maxillofacial Pathology course. At the end of the academic semester, the students completed a questionnaire containing 10 questions regarding the app's use. The study included 123 students. Regarding the devices used to answer the questions on the app, 117 (95.1%) students used a smartphone and 3 (2.4%) used a laptop. Almost all students (121; 98.4%) agreed that this interactive web-based response system provided the teacher with a better overview of students' understanding and improved their self-assessment of the acquired knowledge of the subjects. Most students (118; 95.9%) preferred classes using this technology and 122 (99.2%) stated that using the app made them feel more engaged in classes. In addition, all students agreed that the app improved student-teacher interactions. Most students (119; 96.7%) considered the digital interactive method more attractive than the conventional teaching approach, and 99 (80.5%) did not have any negative comments regarding the app. In conclusion, the Poll Everywhere® app provides a more dynamic and attractive educational environment for Oral and Maxillofacial Pathology teaching.